Teamwork’s Experiences through Project-Based Webinar in English for Public Speaking - Suharto, Ririn Pratiwi (Indonesian Journal Publisher, 2024)
Several problems are faced in the English for Public Speaking course. Lecturer wants to implement project-based webinar which held by students’ teamwork. This research aims to identify the implementation of project-based webinar from teamwork’s experiences to organize webinar in English for Public Speaking course. The researcher conducted qualitative method with basic interpretative approach through observation. This research conducted at D-4 English for Tourism Industry, Politeknik Negeri Malang. The subjects were 18 students of the third semester students. Observation was managed along the process of the Project Based Learning implementation in the English for Public Speaking. The result of this study about teamwork’s experiences are being a chief committee, secretary, treasurer, event division, public relation division, also publication and documentation division. The process of the Project Based Learning implementation by creating webinar gives many advantages for the students. It makes the students become more creative and train to be critical due to the problem which is given is based on real problem faced in that time.